PENGARUH PEMBERIAN SARI KULIT NANAS (Ananas comosus (L) Merr) TERHADAP JUMLAH KOLONI BAKTERI PADA IKAN BANDENG (Chanos chanos F.) - Zainal Berlian; Fitratul Aini; Melda Yunita (Florea: Jurnal Biologi dan Pembelajarannya)
Pineapple rind (Anana chomosus (L) Merr) is household waste has not been used optimally. Rind the Â pineapple contains bromelain enzymes, citric acid and phenols, to inhibit bacterial growth. The research objective test ativitas antibacterial (Ananas chomosus (L) Merr) to fish. The study design used a completely randomized design (CRD), the treatment of P0 (0%), P1 (12.5%), P2 (25%), P3 (50%) and P4 (100%). Results of analysis of variance (ANOVA), the concentration extract pineapple rind (Anana chomosus (L) Merr) gives significant differences (p> 0.01) to the number of bacterial colonies, where Fh > Ft. The results showed pineapple rind (Anana chomosus (L) Merr) has antibacterial activity